Financial Reporting Quality of Chinese Reverse Merger Firms: The Reverse Merger Effect or the China Effect? - CHEN, Kun-Chih (Institutional Knowledge at Singapore Management University, 2013)
In this paper, we examine why Chinese reverse merger (RM) firms have lower financial reporting quality. We find that while U.S. RM firms have similar financial reporting quality as matched U.S. IPO firms, Chinese RM firms exhibit lower financial reporting quality than Chinese ADR firms. We further find that Chinese RM firms exhibit lower financial reporting quality than U.S. RM firms. These results indicate that the use of RM process is associated with poor financial reporting quality only in firms from China, where the legal enforcement is weaker than U.S. In addition, we find that compared to Chinese ADR firms, Chinese RM firms have lower CEO turnover performance sensitivity, a measure of bonding incentives, and poorer corporate governance, which in turn explains the lower financial reporting quality in Chinese RM firms. Overall the results suggest that the RM process provides Chinese firms with low bonding incentives and poor governance the opportunity to access the U.S. capital markets, resulting in poor financial reporting quality in Chinese RM firms.